RANCANG BANGUN SISTEM INFORMASI PENJUALAN PERLENGKAPAN HAJI ALFATH SEMARANG (Information Technology and Telematics, 2013)
Abstract :Alfath Semarang is a Muslim fashion store located in Komplek Ruko Mall Ciputra C.26-27. While this serves only Alfath offline or in other words only serve customers who come directly to Alfath.This study aims to design a web-based application system which contains the procedures of payment and purchase online. Making an application program using web languages with Macromedia Dreamweaver MX, PHP scripts, using MySQL database processing. Of this research effort is expected to create applications on the sale of equipment pilgrimage. And can increase the company's revenue. As well as the promotion system that does not exist in the online company. This website is created to facilitate buyers from within or outside the city who will buy the product from Alfath Semarang, without having to come to Alfath Semarang. Increase convenience in shopping. Keywords: Sales Information System, PHP, Macromedia Dreamweaver MX